Exploring interaction effects of social determinants of health with hospital admission type on academic performance: a data linkage study - Jane Lyons (Archives of Disease in Childhood, 2025)
Objective: To investigate the moderating effects of socio-demographic social determinants of health (SDH) in the relationship between types of childhood hospitalisation (ie, none, injury, non-injury, injury+non-injury) and academic performance. Design, setting and patients: Children residing in Wales 2009–2016 (N=369 310). Secure Anonymised Information Linkage databank linked Tagged Electronic Cohort Cymru (five data sources) from the Wales Electronic Cohort for Children. Main outcome measure: Binary educational achievement (EA) measured across three key educational stage time points: grade 6 (mean age 11 years, SD 0.3), 9 (mean age 14 years, SD 0.3) and 11 (mean age 16 years, SD 0.3). Results: Of the 369 310 children, 51% were males, 25.4% of children were born in the lowest two Townsend deciles. Females were more likely to meet EA than males (adjusted risk ratio (aRR) (95% CI): 1.047 (1.039, 1.055)). EA was lower for injury admissions in males and any admission type in females (interactions: female×non-injury 0.982 (0.975, 0.989); female×injury+non-injury 0.980 (0.966, 0.994)). Children born into a more deprived decile were less likely to achieve EA (0.979 (0.977, 0.980)) and worsened by an injury admission (interactions: townsend×injury 0.991 (0.988, 0.994); Townsend×injury+non-injury 0.997 (0.994, 1.000)). Children with special educational needs (SEN) were less likely to meet EA (0.471 (0.459, 0.484) especially for an injury admission (interactions: SEN×injury 0.932 (0.892, 0.974)). Conclusion: SDH moderated the impact of hospital admission type on educational outcomes prompting future investigation into the viability of in-hospital routine screening of families for SDH and relevant post-hospital interventions to help reduce the impact of SDH on educational outcomes post-hospitalisation.